Corporate Governance Impressions of Third Party Funds and Financial Performance - Juliasari, Deni (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
Financial performance is an important thing that must be achieved by every company because it is reflection of company’s ability to manage and allocate the resources. This performance has a relationship with GCG and DPK. Then this study want to analyze the relationship of GCG and DPK to this performance not only on direct reffect but also on indirect too. This study uses a quantitative approach with path analysis as testing model. The population for this study ia 41 banking companies listed on the Indonesia Stock Exchange 2011-2015,. The sampling technique used purposive sampling technique, then obtained 28 companies that met the criteria, so the total sample was 140 observations (firm-years). The results showed that GCG does not affect company performance but DPK has a positive effect to the performance. Other than that GCG has a positive effect for financial performance with DPK as an intervening variable.